Characterization of ZrO2-Y2O3-MnO2 solid solutions as components for reversible solid oxide cells - Natoli, Alejandro (2019)
Long-term degradation remains the main issue for the viability of reversible solid oxide fuel/electrolysis cell (SOFC/SOEC) technology as practical hydrogen production and energy storage systems. While some lifetime-limiting factors are common in both regimes, the major specific degradation mechanism in SOEC regime relates to the delamination phenomena. The experimental and modelling results suggest that high oxygen pressures can develop in electrolyte near the anode/electrolyte interface resulting in formation of voids at the grain boundaries, intergranular fractures, cracks in anode, and anode delamination; all factors contribute to irreversible degradation. The objective of this work was the characterization of ZrO2-Y2O3-MnO2 solid solution in order to design a functional material with oxygen storage ability that may be used as inclusion into electrolyte membrane or as interlayer between electrolyte and oxygen electrode with the purpose of delay or prevent degradation and irreversible changes. ((ZrO2)1-x(Y2O3)x)1-y(MnOn)y ceramics (x = 0.02-0.05, y = 0.05-0.15) were prepared by solid-state reaction route and sintered in air at 1400-1600°C. XRD results showed the formation of singlephase solid solutions with cubic fluorite-type structure for the compositions with x = 0.05, while the ceramics with lower yttria content comprised 2 or more phases based on different polymorphs of zirconia. The characterization of materials included microstructural studies (SEM/EDS), thermal analysis (thermogravimetry, dilatometry), measurements of electrical conductivity as function of temperature and oxygen partial pressure, and determination of ionic transference numbers by modified e.m.f. method. Increasing Mn content was found to results in increase of the total electrical conductivity and electronic contribution under oxidizing conditions, while ionic transport dominates under reduced oxygen partial pressures. Electrical measurements showed also a slow relaxation of electrical conductivity on redox cycling that possibly can be attributed to a variable solubility of Mn cations in fluorite lattice.